The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1200/jco.2010.30.6308
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome-Wide Studies of Merkel Cell Carcinoma and Validation of Intratumoral CD8+ Lymphocyte Invasion As an Independent Predictor of Survival

Abstract: Purpose Merkel cell carcinoma (MCC) is a polyomavirus-associated skin cancer that is frequently lethal and lacks established prognostic biomarkers. This study sought to identify biomarkers that improve prognostic accuracy and provide insight into MCC biology. Patients and Methods Gene expression profiles of 35 MCC tumors were clustered based on prognosis. The cluster of genes overexpressed in good-prognosis tumors was tested for biologic process enrichment. Relevant mRNA expression differences were confirmed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
266
1
8

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 273 publications
(291 citation statements)
references
References 32 publications
(7 reference statements)
16
266
1
8
Order By: Relevance
“…The importance of the CD8 T cell response against MCC is highlighted by the finding that robust intratumoral (not peritumoral) infiltration of CD8+ TILs is associated with a striking 100% survival in a study of 146 patients [46]. Additional studies have also indicated that MCC TILs, including CD3+, CD8+ T cells, are associated with improved overall and disease-specific survival [47,48].…”
Section: Review Vandeven and Nghiemmentioning
confidence: 96%
See 1 more Smart Citation
“…The importance of the CD8 T cell response against MCC is highlighted by the finding that robust intratumoral (not peritumoral) infiltration of CD8+ TILs is associated with a striking 100% survival in a study of 146 patients [46]. Additional studies have also indicated that MCC TILs, including CD3+, CD8+ T cells, are associated with improved overall and disease-specific survival [47,48].…”
Section: Review Vandeven and Nghiemmentioning
confidence: 96%
“…Additional studies have also indicated that MCC TILs, including CD3+, CD8+ T cells, are associated with improved overall and disease-specific survival [47,48]. Furthermore, expression of genes encoding granzyme A, B, H and K, CCL19, lymphocyte activation genes (SLAMF1 and NKG2D) and CD8α are associated with favorable prognoses, independent of stage [46]. To date, 17 MCPyV-specific CD8 epitopes have been identified, for which 14 HLA-I tetramers have been generated, enabling functional and phenotypic analysis [43,45,49,50].…”
Section: Review Vandeven and Nghiemmentioning
confidence: 99%
“…Factors recognized as associated with poor prognosis are size of the tumor and presence of metastases according to the AJCC staging (4,47,55,(64)(65)(66)(67)(68), and immunosuppression (65,69,70). Recently, histological and immunochemistry markers have been described as potentially associated with poor outcome like low tumor infiltrating CD8 + T cells (101) and P53 and P63 expression and gen mutations (54, 68, 74) ( Table 2).…”
Section: Mcpyv Status and MCC Prognosismentioning
confidence: 99%
“…3 Although multiple microarray studies have provided insights into MCC pathogenesis, molecular events essential to MCC pathogenesis are largely unknown. [4][5][6] Though the principal tenet in cancer is that tumor is initiated and driven by mutations, it is now clear that epigenetic pathways also play a significant role in oncogenesis. Moreover, diverse gene mutations generally converge functionally to deregulate similar core cellular process, which can be targeted by approaching epigenetic vulnerabilities.…”
Section: Introductionmentioning
confidence: 99%